Phylogeny-based species delimitation and integrative taxonomic revision of the Hyalinobatrachium fleischmanni species complex, with resurrection of H. viridissimum (Taylor, 1942). Issue 5 (3rd July 2020) - Mendoza-Henao, Angela M.; Arias, Erick; Townsend, Josiah H.; Parra-Olea, Gabriela
Abstract : Hyalinobatrachium fleischmanni is one of the widest ranging glassfrog species, occurring in the lowlands from Mexico through Central America to Ecuador. Despite its conservative morphology, previous studies suggested that the species is comprised of multiple lineages. Here we test the hypothesis of cryptic species within H. fleischmanni by means of morphology, morphometrics, bioacoustics, and molecular analysis. Molecular delimitation based on mitochondrial and nuclear genes detected 17 candidate species within H. fleischmanni but combined with other sources of evidence, we support the recognition of at least three different species within the name H. fleischmanni . The identity of H. fleischmanni sensu stricto is supported for populations from Costa Rica to eastern Honduras while the name Hyalinobatrachium tatayoi corresponds to the southern lineages in Costa Rica and South America. Those two species differ in the note duration of the advertisement call and in the absence of nuptial pads in the hand webbing of H. fleischmanni males. Populations from Mexico and Guatemala represent a third species to which we assign the available name H. viridissimum comb. nov. Hyalinobatrachium viridissimum differs from H. fleischmanni and H. tatayoi in mitochondrial DNA divergence, variation in peak frequency, and note duration of the advertisement call. A divergent lineage from western and central Honduras is tentatively assigned to H. viridissimum . Based on these results, we provide updated information for each species. http://www.zoobank.org/urn:lsid:zoobank.org:pub:96D65174-4F8B-4E4B-8C85-967767311255